Republic of Armenia : Joint Staff Advisory Note on the Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2008)
This paper presents a Joint Staff Advisory Note on the Republic of Armenia's Second Poverty Reduction Strategy Paper (PRSP). Armenia's poverty and extreme poverty rates declined in 2006 to 26.5 percent and 4.1 percent of the population, respectively-results which surpassed PRSP-1 projections. Inequality also decreased to a rate below the PRSP-1 goal, as measured by a reduction in the Gini coefficient from 0.395 in 2004 to 0.369 in 2006. Prudent fiscal and monetary policies were instrumental in maintaining macroeconomic stability and contributing to poverty reduction.